Transfer of academic information literacy skills to workplace contexts - Fourie, Ina; Julien, Heidi (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2019)
This paper reports preliminary results of a study analyzing transfer of information literacy skills learned in a compulsory undergraduate course at the University of Pretoria. Twenty-three alumni with a range of disciplinary backgrounds, and currently working in a diversity of workplaces, participated in critical incident interviews which explored transferability of the skills learned in the course, and information practices in the workplace.